القيادة السياسية المعاصرة من المنظور الإسلامي دكتور محاضير محمد أنموذجا - Anwer Mohamed Abi Janah
This study examined the contemporary political leadership of Tun Dr Mahathir Mohamed according to the Islamic perspective. Tun became the fourth Prime Minister of Malaysia from year 1981 to 2003 and was one of the most prominent leaders in the Islamic world. During his tenure of leadership, Malaysia gained various political, economical and social recognitions in the region, as well as in the international arena. Inspite of the economic and political crisis in the region, Tun was able to maintain his premiership even with strong resistance fiom the opposition parties. Indeed Tun has managed to steer the country out of the most difficult economic turmoil faced by the region. Additionally, this research also studied Tun's concept of leadership and the various components formed from political, humanity and competencies point of view, in which that it emphasised on the principal factors of YAB Tun Dr Mahathir's leadership and personality. This study attempted to discover the implications of Islamic teachings in Tun's personality during his premiership. The methodology of this study was based on the deduction and analysis of historical data. The study found that the the concept of leadership in Islam, apparently covers every aspects of social segments, be it in community, family and individual that have be portrayed by Tun Dr Mahathir in his leadership. Although he attained recognitions and excelled domestically and internationally, yet he continued receive criticisms within and from the outside of the country. In conclusion, the study proposed that an in-depth research shall be performed on Tun's political and economical philosophies, as well as his strategies in resolving Malaysia's political and economic crisis. Hence, the research to be translated into Arabic for the benefits of the society